2019
DOI: 10.1016/j.jaci.2019.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Advances in asthma and allergic disease genetics: Is bigger always better?

Abstract: This review focuses on genome-wide association studies (GWASs) of asthma and allergic diseases published between January 1, 2018, and June 30, 2019. During this time period, there were 38 GWASs reported in 19 articles, including the largest performed to date for many of these conditions. Overall, we learned that childhood-onset asthma is associated with the most independent loci compared with other defined groups of asthma and allergic disease cases; adult-onset asthma and moderate-to-severe asthma are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 82 publications
(190 reference statements)
1
70
0
4
Order By: Relevance
“…Epidemiological studies indicate that asthma and allergic disease co-occur and share a similar and very close course especially in the children (Ober and Yao, 2011;Guibas et al, 2017;Schoettler et al, 2019). It is reported that allergic asthma is most common in kinds of diseases in childhood (Cookson and Moffatt, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that asthma and allergic disease co-occur and share a similar and very close course especially in the children (Ober and Yao, 2011;Guibas et al, 2017;Schoettler et al, 2019). It is reported that allergic asthma is most common in kinds of diseases in childhood (Cookson and Moffatt, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Schoettler et al, in the GWAS of asthma, a larger sample size with heterogeneous subtypes is not necessarily better than a smaller sample size for homogeneous subtypes to identify the relevant genetic variants because the genetic background between asthma subtypes may be different. 24 Thus, investigating the shared genetic contribution to coexistent diseases or traits (eg, allergic disease, obesity) and specific asthma subtypes (eg, allergic asthma, obesity-associated asthma phenotype) would boost the power to detect subtype-specific variants that would have been masked by a traditional single-disease GWAS ( Fig 1 ). A comprehensive characterization of these shared genetic architectures would improve understanding of the multiple dimensions of asthma pathobiology.…”
Section: Asthma Heterogeneity and Its Related Geneticsmentioning
confidence: 99%
“…Genetic and epigenetic variation of the host play key roles (Willis-Owen et al, 2018), and airway dysbiosis may be an important trigger (Huang et al, 2015). Childhood-onset asthma appears to be triggered by allergic and infective immune responses, and barrier dysfunction, with a stronger genetic component and higher heritability (Pividori et al, 2019;Schoettler et al, 2019). Genome-wide association studies (GWAS)s have focused on childhood-onset allergic asthma, and the currently identified single nucleotide polymorphisms (SNP)s thus seem to have lower significance in adult-onset asthma (Pividori et al, 2019).…”
Section: Genome-scale Epithelial Factors Behind Airway Diseasesmentioning
confidence: 99%
“…The risk factors for asthma include AR and allergic conjunctivitis, atopic dermatitis, exposure to air pollution, cigarette smoke, occupational risk factors, obesity, and genetic factors (Polosa and Thomson, 2013;Ilmarinen et al, 2015;Toskala and Kennedy, 2015;Willis-Owen et al, 2018;Toppila-Salmi et al, 2019). Childhood-onset asthma has a stronger genetic component than adult asthma and is triggered due to dysregulated allergy and epithelial barrier function (Pividori et al, 2019;Schoettler et al, 2019). The development of adult asthma is more likely in patients with an accumulation of several risk factors and with allergic multimorbidities (Hallit et al, 2019;Pividori et al, 2019;Toppila-Salmi et al, 2019).…”
Section: Environmental Factors Epithelium and Asthmamentioning
confidence: 99%